Low-impact (compliant) flooring and staff injuries. Issue 7 (27th March 2022) - Hanger, H. C.; Wilkinson, Tim J.
Abstract: Introduction: Low impact flooring (LIF) has shown potential for reducing fall-related injuries for older people in residential care or hospital environments. However, the increased rolling resistance when moving equipment on these floors has raised concerns that staff injuries may increase. Methods: LIF was trialled on one Older Persons Health ward for 2.5 years. Reported staff injuries were monitored during and following the trial. Numbers of staff injured on the LIF ward were compared with three other similar and adjacent OPH wards without LIF for the duration of the trial ('concurrent control' evaluation). At the trial conclusion the LIF ward moved to a different hospital that had standard flooring. This enabled a further 'during and after' evaluation where numbers of staff injured from the LIF ward during the trial were compared with those reported afterwards by the same ward staff without LIF. Results: There was no difference in the numbers of staff injured in the LIF ward compared with the concurrent control wards (28 LIF vs 30 control; p  = 0.44). The number of staff with injuries in the LIF ward also did not significantly alter when those staff moved to a new ward without LIF (45 after vs 28 before; p  = 0.11). Conclusion: There was no change in the numbers of staff with injuries during the LIF trial in an Older Persons Health ward. This small study suggests LIF appears safe for both patients and staff. Implications for rehabilitation: Falls in hospital are common with patient injuries occurring in approximately 20-30% of falls. Low impact (compliant) flooring may reduce fall-related injuries in hospitals and residential care. Low impact flooring has an increased rolling resistance, which has the potential to increase staff injuries when moving equipment. This study found no change in the number of staff injured during a low impact flooring trial providing some reassurance that these floors are safe for staff.